The Unconquerable Sun: An introduction to Koinon III and brief note concerning the solace of numismatics - Molinari, Dr Nicholas J. (KOINON: The International Journal of Classical Numismatic Studies, 2020)
If this year can be described in one word, it would be upheaval— for the first time in my life, it is more difficult than ever to imagine what the world might look like by the time our next volume sees print in late 2021, and I’d imagine folks living under the reign of Caracalla felt even greater uncertainty. He was, by all accounts, a vicious tyrant and downright terrible human being. As Dio Cassius describes him: ‹He never loved anyone, but he hated all who excelled in anything, most of all those whom he pretended to love most› (Roman History 11.6). He was said to have an unquenchable thirst for blood, be it animals or even humans, and allegedly killed innumerable people, including his fatherly tutor, Clio, and his own brother, Geta. After Geta’s assassination, as all students of Roman coinage surely know, Caracalla issued a damnatio memoriae, thereby removing all vestiges of the sibling throughout the empire—though he couldn’t get to all the coins. His message on the above aureus seems fairly simple, namely, that the emperor was as unconquerable as the sun, and this message would have undoubtedly struck fear into as many people as it gave hope (if there were any in the latter camp at this stage in his reign). And yet, despite how horrible things were during Caracalla’s reign, the sun did rise again; it was Caracalla who did not.